Phage combination therapies for bacterial wilt disease in tomato - Wang, Xiaofang; Wei, Zhong; Yang, Keming; Wang, Jianing; Jousset, Alexandre; Xu, Yangchun; Shen, Qirong; Friman, Ville-Petri (Nature biotechnology, 2019)
Bacteriophages have been proposed as an alternative to pesticides to kill bacterial pathogens of crops. However, the efficacy of phage biocontrol is variable and poorly understood in natural rhizosphere microbiomes. We studied biocontrol efficacy of different phage combinations on Ralstonia solanacearum infection in tomato. Increasing the number of phages in combinations decreased the incidence of disease by up to 80% in greenhouse and field experiments during a single crop season. The decreased incidence of disease was explained by a reduction in pathogen density and the selection for phage-resistant but slow-growing pathogen strains, together with enrichment for bacterial species that were antagonistic toward R. solanacearum . Phage treatment did not affect the existing rhizosphere microbiota. Specific phage combinations have potential as precision tools to control plant pathogenic bacteria. Phage combination therapies reduce bacterial wilt disease incidence in tomato by up to 80%.